Geospatial technology for flood hazard analysis in Comal Watershed, Central Java, Indonesia - Wibowo, Y. A. (2022)
River flood has become a severe disruption toward the community, and it can trigger loss of life, damage infrastructure and properties, suffer economic, social and cultural, and environmental degradation. Flood hazard analysis downstream of Comal Watershed in Pemalang Regency, Central Java, was designed to generate the flood hazard map to reduce the effects of flood disaster. The flood hazard was simulated for five, 10, 25, and 50 years using HEC-RAS and ArcGIS with HEC-GeoRAS. The data input was discharge, geometry, and roughness. The discharge was obtained from hydrology modelling by utilizing daily rainfall data for 22 years. The geometry data was composed of a topographic map and measured using an echo sounder, while the roughness was from land use along the flood plain. The accuracy and validation were conducted by matching the flood modelling result with the historical data from the Pemalang Disaster Management Agency and in-depth interview results with the community. The results showed the Comal River downstream flood hazard was feasible for disaster risk reduction purposes. The flood hazard levels were generated in five, 10, 25, and 50 years return periods dominated by high and very low levels. In every return period, the rising trend of the inundation width and the flood depth occurred for very high, high, and very low levels.